TREND DAN PERAMALAN PRODUKSI DAN KONSUMSI DAGING SAPI DI PROVINSI SUMATERA BARAT - Oktavia, Hanifah Tri; Darnetti; Alfikri (Green Engineering Society, 2024)
The objectives of this study are (1) to identify the trend of beef production in West Sumatera, (2) to identify beef consumption in West Sumatera, and (3) to estimating of beef production and consumption in West Sumatera. This study uses secondary data from Badan Pusat Statistik of West Sumatera and Dinas Peternakan dan Kesehatan Hewan of West Sumatera. Secondary data were processed with qualitative analysis techniques in a narrative manner to determine the trend of beef production and consumption from 2004 to 2023 and quantitatively to determine the estimated production and consumption of beef in West Sumatera in 2024-2028. The result of the study is the trend of beef production in West Sumatera in the last 20 years is 928,798 kg/ year or grows by 5,1%. The trend of beef consumption in West Sumatera in the last 20 years was 329,874/ year or grew by 4,2%. Estimated beef production in West Sumatera experienced a growth of 2,2% or 547,648 kg/ year, the estimated production can meet the estimated consumption which grew by 1,9% or 329,874 kg/ year.